Gli3 Repressor Controls Cell Fates and Cell Adhesion for Proper Establishment of Neurogenic Niche - Hui Wang; Anna W. Kane; Cheol Lee; Sohyun Ahn (Cell Reports, 2014)
Neural stem cells (NSCs) in the subventricular zone (SVZ) rely on environmental signals provided by the neurogenic niche for their proper function. However, little is known about the initial steps of niche establishment, as embryonic radial glia transition to postnatal NSCs. Here, we identify Gli3 repressor (Gli3R), a component of the Sonic hedgehog (Shh) pathway, as a critical factor controlling both cell-type specification and structural organization of the developing SVZ. We demonstrate that Gli3R expressed in radial glia temporally regulates gp130/STAT3 signaling at the transcriptional level to suppress glial characteristics in differentiating ependymal cells. In addition, Gli3R maintains the proper level of Numb in ependymal cells to allow localization of cell adhesion molecules such as vascular cell adhesion molecule (VCAM) and E-cadherin. Thus, our findings reveal a role for Gli3R as a mediator of niche establishment and provide insights into the conditions required for proper SVZ neurogenic niche formation.